Screening Design of Experiments of AGET ATRP of Butyl Methacrylate in a Stirred Emulsion Reactor. Issue 1 (5th October 2021) - Awad, Mohammed; Dhib, Ramdhane; Duever, Thomas
Abstract: This study investigates the ab initio atom transfer radical polymerization of butyl methacrylate using activator generated by electron transfer in a well‐mixed 2 L emulsion reactor. A first time reported polymerization system initiates by a catalyst complex with hexamethylenetetramine as a ligand and in presence of sodium dodecyl sulfate as an anionic surfactant. The system shows a relatively low monomer conversion rate of 14% and a controlled number average molecular weight ( M n ) of 8 kg mol −1 with a polydispersity index ( Ð ) of 1.24 for 2 h reaction time. A statistical design of experiments is followed to study the effects of reaction temperature, surfactant amount, stirring speed, and ligand amount to assess their impact on the monomer conversion, M n, and Ð . A fractional factorial with a resolution IV design is adopted and an empirical regression model is developed from eight experimental trials. The results tell that the reaction temperature has the greatest influential on the process outputs. Also, the surfactant amount and stirring speed strongly affect the conversion rate, while the ligand amount strongly affects the M n and Ð . The results also show that the temperature–surfactant interaction is the most significant on the conversion rate and M n . Abstract : A proper choice of ligand and surfactant is necessary to ensure a controlled atom transfer radical polymerization is achieved in emulsion media. Two‐level fractional factorial statistical design of experiment is an efficient path to screen and predict the product characteristics yields from complex polymerization methods. The reaction temperature is a key factor on the overall process outputs.